22.0k views
5 votes
If P(x) = 3x
4 + 7x
3 − 2x
2 + 5x − 7, find:

i) P(−2)

User Perseus
by
5.6k points

1 Answer

2 votes

Answer:

The value of c so that (x + 1) is a factor of the polynomial p(x) = 5x^4 + 7x^3– 2x^2– 3x + c is equal to 1

Solution:

Given polynomial is as follows

Also given that (x+1) is factor of given polynomial p(x).

Need to determine value of constant c.

We will be solving above problem using factor theorem.

Factor theorem says that if ( x – a) is a factor of any polynomial f(x) , then f(a) = 0.

As in our case f(x) = p(x) and factor of p(x) is (x + 1) , which can be rewritten as (x – ( -1)) , so "a" in our case is -1 .

According to factor theorem p(-1) = 0

On substituting x = -1 , in given expression of p(x) we get

Hope this helps you

Explanation:

User Martin Bauer
by
5.4k points